Direct and converse magnetoelectic effect in laminate bonded Terfenol-D-PZT composites - Record, Paul M.; Popov, Chris; Fletcher, John E.; Abraham, Eitan; Huang, Zhaorong; Chang, Harrison Hoon Seok; Whatmore, Roger W. (Elsevier Science B.V., Amsterdam., 2007)
Results from measurements of the direct and converse magnetoelectric (ME) effect on a three-layer, epoxy-bonded, laminate composite are presented. The laminae are a single transversely polarized piezoelectric elements (PZ29) sandwiched between two longitudinal-magnetic ally polarized magnetostrictive TD elements (Terfenol-D-TX GMM). The direct ME effect was determined by measuring laminate output with a Helmholtz-generated AC field (up to 7 Oe) in the range 50 Hz-100 kHz biased by a DC field (0-1000 Oe). Peak voltage output occurred at the sample's mechanical resonant frequency, its value depending on the strength and direction of the applied magnetic field. The peak output was 3061 mV at 3 Oe AC field and 1000 Oe bias, equivalent to 74.4 V cm(-1) Oe(-1). The peak output coefficient, however, was 93.6 V cm(-1) Oe(-1) at 0.1 Oe AC field and 1000 Oe DC bias. The reduction at higher drive amplitudes was attributed to increased Young's modulus of the TD phase. Anomalous peaks in the low frequency spectrum of sample's output are explained. The converse magnetoelectric effect was measured by recording the voltage induced in a solenoid encompassing the ME while exposed to a DC bias field and the PZ phase driven by a 10 VAC source. The peak output is shown to depend on the strength of the applied DC magnetic field and developed a maximum field of 15.4 Oe at the sample's mechanical resonant frequency. This equates to a converse magnetoelectric coefficient of 55 Oe cm kV (-1) (c) 2007 Elsevier B.V. All rights reserved.
Keywords: magnetoelectric effect; magnetoelectric composites; magnetostriction; piezoelectricity; MEMS